Technological competitiveness of the EU member states in the era of the fourth industrial revolution - Weresa, Marzenna Anna (Economics and Business Review, 2019)
The aim of this paper is to investigate the implications of the fourth industrial revolution for technological competitiveness, its definition and measurement methods. An empirical part is aimed at identifying comparative advantages of the European Union in digital technologies. Recently new approaches have appeared to measure digital competitiveness, however they use a broad definition of competitiveness that encompasses not only technological factors but also the macroeconomic and institutional environment (IMD, 2017; WEF, 2018). There is still a limited number of studies focused on the technological dimension of competitiveness in digital technologies. This paper fills the gap by developing a conceptual framework based on patent indicators, i.e. Patent Share and Revealed Technological Advantage indices. It allows a consistent analysis of the comparative advantages of the EU member states in digital technologies to be conducted. The results confirm a huge diversity within the EU in terms of digital technologies, their global impact and comparative advantages.